(3caGjI GdeMJGL ef GdWdGH Edi eYQag GdeSGFd GdadcjI HGdMSGHs - (3MSf Hf Ndjd Hf eRQhY, CHh eMeO, TeS GdOjf GdWHfj GdcQGOjSj,J (B887 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3agPg QSGdg MSGHjg eTJedg Ydi bhGYO cdjg ai GSJNQGL GdeSGFd Gdadcjg s
(3BNQgG (B:s
(3dGJNQL Yf GdCYOGO GdePchQg hbO jSQ Gddg HEceGd eG ChQOJg Ydi fMh eG CQOJg s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B189 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B223s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B129 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B90 s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs